The peculiar revolution : rethinking the Peruvian experiment under military rule - Aguirre, Carlos, 1958-; Drinot, Paulo (University of Texas Press, 2017)
On October 3, 1968, a military junta led by General Juan Velasco Alvarado took over the government of Peru. In striking contrast to the right-wing, pro--United States/anti-Communist military dictatorships of that era, however, Velasco's'Revolutionary Government of the Armed Forces'set in motion a left-leaning nationalist project aimed at radically transforming Peruvian society by eliminating social injustice, breaking the cycle of foreign domination, redistributing land and wealth, and placing the destiny of Peruvians into their own hands. Although short-lived, the Velasco regime did indeed have a transformative effect on Peru, the meaning and legacy of which are still subjects of intense debate. The Peculiar Revolution revisits this fascinating and idiosyncratic period of Latin American history. The book is organized into three sections that examine the era's cultural politics, including not just developments directed by the Velasco regime but also those that it engendered but did not necessarily control; its specific policies and key institutions; and the local and regional dimensions of the social reforms it promoted. In a series of innovative chapters written by both prominent and rising historians, this volume illuminates the cultural dimensions of the revolutionary project and its legacies, the impact of structural reforms at the local level (including previously understudied areas of the country such as Piura, Chimbote, and the Amazonia), and the effects of state policies on ordinary citizens and labor and peasant organizations.